2017
DOI: 10.1371/journal.pone.0190068
|View full text |Cite
|
Sign up to set email alerts
|

Urinary exosomal viral microRNA as a marker of BK virus nephropathy in kidney transplant recipients

Abstract: ObjectiveBkv-miR-B1-5p, one of the microRNAs encoded by BK virus, was recently reported to be elevated in the blood among the patients with BK virus nephropathy (BKVN). Urinary exosome was suggested to be a possible source of biomarker for kidney diseases, but it was unknown whether it could contain viral microRNA as well as human microRNAs. The aim of this study was to evaluate whether urinary exosomal BK viral microRNA were expressed during replication and could be used to diagnose BKVN in kidney transplant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 31 publications
0
47
0
Order By: Relevance
“…Moreover, miRNAs of BKPyV and the closely related JCPyV miRNAs have been detected in blood, urine and cerebrospinal fluid samples, often together with the corresponding viral loads with few cases reporting the nature of the NCCR structures [ 42 , 43 ]. It has been suggested that urinary exosomes associated BKPyV -miRNA may be a surrogate marker for BKPyV pathology [ 44 ]. Thus, the association between miRNAs and exosomes has also raised questions about their regulatory potential in non-infected neighbouring cells [ 43 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, miRNAs of BKPyV and the closely related JCPyV miRNAs have been detected in blood, urine and cerebrospinal fluid samples, often together with the corresponding viral loads with few cases reporting the nature of the NCCR structures [ 42 , 43 ]. It has been suggested that urinary exosomes associated BKPyV -miRNA may be a surrogate marker for BKPyV pathology [ 44 ]. Thus, the association between miRNAs and exosomes has also raised questions about their regulatory potential in non-infected neighbouring cells [ 43 , 45 , 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies of urinary chemokines, including CXCL9 and CXCL10, have shown potential benefit and correlate with our own centre experience. Similarly, urine exosomal microRNA signatures, urine proteinase inhibitor 9 (PI 9) mRNA, cellular assays for IFN‐gamma, and plasma donor‐derived cell‐free DNA have all demonstrated the ability to differentiate between various immune‐mediated causes of transplant dysfunction. Furthermore, developments in urine proteomic profiling from Pittsburgh show promise in differentiating BKVN from acute rejection .…”
Section: Diagnostic Challengesmentioning
confidence: 99%
“…Several biomarkers had been proposed in order to enable noninvasive diagnosis of definitive BKN without the risk of renal biopsy; these include heat shock protein 90alfa, CXCL9, neutrophil gelatinase-associated lipocalin, urinary exosomal biomarkers, urinary VP1, and urinary Haufen [65][66][67].…”
Section: Biomarkers Of Bknmentioning
confidence: 99%
“…BK virus VP1 mRNA and urinary exosomal miRNA biomarkers have been described as potential surrogate markers for the diagnosis of PVN, with high sensitivity and specificity for BKN [66,67]. Detection of additional urine biomarkers not only offers additional strategies for noninvasive PVN diagnosis but might also predict graft outcome.…”
Section: Biomarkers Of Bknmentioning
confidence: 99%